(untitled) (Bangladesh Journal of Medical Microbiology, 2009)
The prevalence of sexually transmitted diseases (STDs) among patients attending out patients department of Skin and Venereal diseases of Dhaka Medical College Hospital, Dhaka and Shahid Sohrawardy Hospital, Dhaka was studied. A total of 230 patients were enrolled in the study during the period of July, 2006 to May, 2007. Urethral and endocervical swabs were collected from the participants for detection of Neisseria gonorrheae (by culture), Chlamydia trachomatis (by immunochromatoghraphy) and blood samples for the detection of Treponema pallidum antibody (by rapid plasma regain and Treponema pallidum haemagglutination assay), Herpes simplex virus type 2 antibody (both IgM and IgG by enzyme linked immunosorbent assay) and Human Immunodeficiency virus antibody (by enzyme linked immunosorbent assay). Socio-demographic data and data regarding high-risk sexual behavior were also collected. Out of 230 participants, 199 (86.5%) were positive for STDs pathogens studied, among them, 98 (42.6%) were infected with single pathogen and 101 (43.9%) were suffering from multiple infections. The prevalences of N. gonorrheae, C. trachomatis, T. pallidum, and HSV type 2 were 90 (39.1%), 110 (47.8%), 28 (12.2%) and 88 (38.2%) respectively. However, none of them were positive for HIV infection. Use of condom was significantly associated with protection of the participants against STDs. Keywords: Sexually Transmitted Diseases, Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum, Herpes simplex virus type-2, Human Immunodeficiency virus doi: 10.3329/bjmm.v3i1.2968 Bangladesh J Med Microbiol 2009; 03 (01): 27-33